(untitled) (Journal of actual problems of jurisprudence, 2020)
Abstract. This article provides a holistic analysis of cooperation between the Republic of Kazakhstan and the UN. This study examines a holistic system of relations starting with the development of independent Kazakhstan as a participant in international relations, and ends with an analysis of current trends and the direction of political and economic interaction between the Republic and the UN. In this work, special attention was paid to problematic issues, as well as to the prospects for further cooperation between Kazakhstan and the UN, in the framework of the development of international cooperation. Today, considering the development of international law, it should be noted that Kazakhstan, in the framework of the activities of large international organizations, is actively involved in their activities, and is also a stably developing state. The integral relevance of the article is determined by the need to study the contribution of the Republic of Kazakhstan to the development of modern international relations and international law. One of the important organizations regulating the processes of international interaction between countries is the United Nations. In the current conditions of globalization, as well as the ever-increasing independence of individual states, issues of regulation of relations between countries become the most acute problems affecting world geopolitics. In this regard, the role of individual states and countries in organizing stable international relations in the world is growing. In this case, Kazakhstan has already managed to establish its own position in the international arena as an open and peace-loving state. Kazakhstan’s refusal of nuclear weapons made a significant contribution to the nuclear disarmament process, the cessation of nuclear testing and the strengthening of the nuclear non-proliferation regime. The progressive formation of the economic and political systems of the state, active work in leading international organizations allowed the Republic to gain significant experience and political authority on the world stage. Kazakhstan’s well-known initiatives in the field of sustainable development allow the Republic to position itself as a state committed to peaceful policy, as well as having the main goal of creating full and good-neighborly relations with other countries. Key words: United Nations, UN Charter, UN General Assembly, UNESCO, CICA, Nuclear Non- Proliferation Treaty, UN peacekeeping operations, protection of human rights, gender equality.